Using Cohen Sutherland Line Clipping Algorithm to Generate 3D Models from 2D - Marah Taha (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper provides an efficient algorithm to generate three dimensional objects from simple uncomplicated 2D environment, lead to reduce processor effort, limit of using complex mathematical operations. Most of the previous researches used the idea of ​​drawing by vanishing point to generate 3D objects from 2D environment, But the algorithm designed in this paper provides an idea of ​​how to draw three-dimensional shapes from two-dimensional drawings when applying Cohen Sutherland Line clipping algorithm, so that a basic two-dimensional shape is inserted from a set of points connected with each other must be within vision borders with a vanishing point outside of vision that is connected with all points of basic shape to consist a group of lines with partial intersections. So that any point has specific limited vision border which represents one of its coordinates of depth vertex, finally 3d object is generated when all clipping processes are completed to obtain other coordinates for all points.